Research on Load Checking of In-service Pressure Vessel Nozzle. Issue 1 (June 2020) - Pu, Zhe; Ren, Bin; Tang, Xiaoying; Wang, Jifeng
Abstract: Pressure vessel is an important part of industrial production. Pressure vessels usually have many nozzles, which are connected to other devices through pipeline. Due to the large thermal stress caused by the thermal expansion of the pipeline, the load on the nozzle of the connected vessel will be increased. When the load on the nozzle is too large, it may cause local deformation of the vessel, or even cause cracking at the root of the nozzle. Increasing the flexibility of the pipeline can reduce the load on the nozzle. Taking the flare system of the factory as an assessment case, this paper introduced a new load checking method. The software was used to simulate the load on the liquid separation tank connected with the flare gas pipeline. The calculated load of the liquid separation tank nozzle met the technical conditions of the manufacturer.